Estudo anatômico e morfométrico dos folículos testiculares de algumas espécies de Triatominae (Hemiptera: Reduviidae) - Gonçalves, Teresa Cristina Monte (1986)
Analysis of the length of testis of triatomines, whose lengths (long, medium and short) and thicknesses (thick and thin) vary considerably between the genera, and little between the species. A total of 336 species of triatomines were observed, since the majority of the material belongs to the Triatominae Laboratory Colony of Entomology Departament of Oswaldo Cruz Institute. Due to the difficulty in obtaining this material, the investigation was limited to only two species: R. nasutus – colony of Biology Department of Federal Piaui University and P. megistus brought from the field, Bonfim and Papagaios Municipal (MG). The testicular follicles present itself, in accordance with the genera, in the following way: Rhodnius spp – two long thick and five short thin; Triatoma spp – two long thin, two medium thick and three short thin; Panstrongylus spp – seven, almost identical. ln the first case, the three– genera show significant difference (P> 0,001) in the differents type of testicular follicles, except Triatoma spp, to the long and thin follicles (P> 0,05). In the second case, all the comparisons shown a significant difference (P >0,01), meanwhile, in the other, the significance level diverged: P> 0,005 – R. neglectus X R. ecuadoriensis, in short and thin follicles; P> 0,01 – T. sordida X T. pseudomaculata and T. sordida X T. vitticeps, in medium and thick follicles and T. brasiliensis X T. vitticeps, in short and thin follicles; P>0,05 – R. neglectus X R. Ecuadoriensis, in long and thick follicles, R. nasutus X R. ecuadoriensis in short and thin follicles; P<0,001 (not significative) T. brasiliensis X T. vitticeps, in medium and thick follicles. ln the third case, the significant difference took place only in Rhodnius nasutus, in long and thick follicles (P>0,001) These results didn ' t demonstrate possibilities to use this character in Systematics, although they were promising to Phylogeny studies, since a great number of species shall be observed.